Desain Aplikasi Database Sistem Informasi Akuntansi Sekolah pada Yayasan Ainur Rahmah - Firman Surya; Elfitri Santi; Fera Sriyunianti; Randy Heriyanto (Akuntansi dan Manajemen, 2023)
This study aims to develop an accounting information system database application for Ainur Rahmah Foundation school in West Pasaman, West Sumatra Province. The problem faced by the Ainur Rahmah Foundation is the absent of an information system to manage student data, tuition fees, admission of new students, receipt and disbursement of cash, purchase and use of consumables, acquisition and depreciation of fixed assets. The developed accounting information system database application consists of two main subsystems, namely the back-end and front-end. The back-end system uses DBMS MySQL Server 8.0 while the front-end system is developed using Microsoft Access 2010. Application modules and reports are developed on the front-end using the Visual Basic for Application programming language which is available in Microsoft Access database tools. Applications that have been developed are then tested for use by users to find out if there are errors and adjustments that must be made. After making adjustments based on the user trial stage, the application can be accepted by users and can be operated according to needs.